Olfactory cues play a significant role in removing fungus from the body surface of Drosophila melanogaster. - Yanagawa, A.; Chabaud, M.A.; Imai, T.; Marion-Poll, F. (Journal of Invertebrate Pathology, 2018)
Many insects and Dipterans in particular are known to spend considerable time grooming, but whether these behaviors actually are able to remove pathogenic fungal conidia is less clear. In this study, we examined whether grooming serves to protect flies by reducing the risk of fungal infection in Drosophila melanogaster. First, we confirmed that fungi were removed by grooming. Entomopathogenic, opportunistic, and plant pathogenic fungi were applied on the body surface of the flies. To estimate grooming efficiency, the number of removal conidia through grooming was quantified and we successfully demonstrated that flies remove fungal conidia from their body surfaces via grooming behavior. Second, the roles of gustatory and olfactory signals in fungus removal were examined. The wildtype fly Canton-S, the taste deficiency mutant poxn 70, and the olfactory deficiency mutant orco1 were used in the tests. Comparisons between Canton-S and poxn 70 flies indicated that gustatory signals do not have a significant role in fungal removal via grooming behavior in D. melanogaster. In contrast, the efficiency of conidia removal in orco1 flies was drastically decreased. Consequently, this study indicated that flies rely on mechanical stimulus for the induction of grooming and olfaction for more detailed removal.